A new species of the fishfly genus Neochauliodes van der Weele discovered from southwestern China through an integrative approach based on morphological and molecular evidence (Megaloptera: Corydalidae: Chauliodinae) - Tu, Yuezheng; Liu, Xingyue (Zootaxa, 2021)
Neochauliodes van der Weele, 1909 is the largest genus of the subfamily Chauliodinae of the megalopteran family Corydalidae, currently with 47 described species. Here we report Neochauliodes triangulatus sp. nov. from western Yunnan, China. The new species belongs to the Neochauliodes bowringi species-group and is confirmed to be different from the other species of this group based on morphological and molecular evidence.